The Motivation for Learning English Among Second and Third Year Students at Souphanouvong University - LADDAVONE, vilasack (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to investigate the level of motivation in learning English among second- and third-year students at Souphanouvong University, focusing on both intrinsic and extrinsic motivation. The sample consisted of 228 students from various faculties. A questionnaire was used as the primary instrument for data collection. The collected data were analyzed using frequency, percentage, mean, and standard deviation. The findings revealed that, overall, the students demonstrated a high level of motivation in learning English (????̅ = 4.00, SD = .88). Extrinsic motivation showed a higher mean score than intrinsic motivation, with mean scores of 4.16 (SD = .87) and 3.84 (SD = .89), respectively. These results indicate that students were mainly motivated by external factors, such as obtaining better job opportunities, pursuing higher education, and communicating with foreigners. Regarding intrinsic motivation, the highest-rated factor was self-improvement (????̅ = 4.08, SD = .82), followed by confidence in using English (????̅ = 3.99, SD = .87) and enjoyment of learning English (????̅ = 3.75, SD = .89). For extrinsic motivation, the highest-rated factor was using English to obtain a good job (????̅ = 4.35, SD = .80), followed by future job applications (????̅ = 4.22, SD = .84) and opportunities for studying abroad (????̅ = 4.21, SD = .93). In contrast, learning English primarily for achieving good examination scores received the lowest mean score (????̅ = 3.80, SD = .92), although it remained at a high level. In conclusion, second and third-year students at Souphanouvong University demonstrated a high level of motivation in learning English. Career advancement, further education, and practical use of English in real-life situations were identified as the key motivating factors encouraging students to improve their English language skills in order to achieve their academic and professional goals in the future.